Experiences Of Women With Infertility And Their Bio-Psychosocial Management: A Study At The Korle-Bu Teaching Hospital - Kussiwaah, D.Y (University of Ghana, 2016)
Research has shown that infertility affects millions of people worldwide and it is considered as one of the most difficult life experiences and a bio-psychosocial crisis encountered by most couples. It is also known to have serious consequences on both the psychological and the social safety of women in Africa and the world at large. However, literature about the bio-psychosocial management of women with infertility is scanty in Ghana, especially the aspect of psychosocial management of these women. The purpose of this study was to explore the experiences of these women psychologically, socially, the sort of biological management given to them, and finally the psychosocial management that are being rendered to them at the Korle-Bu Teaching Hospital. The bio-psychosocial model was used as a guiding framework to understand the experiences of these women and whether they were managed bio-psychosocially. This study utilized a qualitative exploratory descriptive approach to conduct a semi-structured interview on fourteen (14) women who were purposively selected. Interviews were audio taped, transcribed verbatim and analysed using thematic content analysis. Five (5) themes and twenty two (22) sub-themes were identified. Out of these, one (1) other theme which was not related to the model used, emerged out from thematic content analysis. The findings from the study indicated that, women with fertility problems experienced difficulties in all aspects of their lives and were emotionally burdened with loneliness, anxiety, depression, lack of concentration, worrying and thinking, less sexual satisfaction, stigmatization, intentional isolation, inability to attend social functions and marital instability. Meanwhile, their management was solely biological or medical whereas their psychosocial needs, of which they rather yearn for, were neglected in their care. The findings of this study have implications for nursing practice, nursing education, nursing research and policy formation.
Thesis (MPhil)
Keywords: Women; Experiences; Infertility; Bio-Psychosocial; Management; Korle-Bu Teaching Hospital; Ghana